ANALISIS KESETARAAN GENDER DALAM JABATAN PUBLIK PADA DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA KUPANG - Irenius Bogo; Laurensius P. Sayrani; Rouwland A. Benyamin (PT. Hasba Edukasi Mandiri, 2025)
The struggle for gender equality in Indonesia is still constrained by perspectives that associate women primarily with domestic roles, thereby limiting their participation in the public sphere. This study aims to analyze the implementation and model of gender equality in public office at the Office of Population Control and Family Planning (DP2KB) of Kupang City, an institution with a balanced composition of employees—50% men and 50% women. The research applies a qualitative-descriptive method with a case study approach. Research informants consisted of 11 key individuals (ranging from the Head of Office to Section Heads) selected purposively. The analysis focuses on six indicators of female leadership: Direction Setting, Influencing Ability, Team Building, Risk Taking, Motivation, and Emotional Intelligence.The findings reveal that DP2KB Kupang City has achieved significant progress through female leadership in strategic positions. The leadership model practiced is proven to be transformative, inclusive, and adaptive. Specifically, this leadership is characterized by: Direction Setting through collaboration and inclusive team involvement; Influencing Ability based on empowerment; and the use of Emotional Intelligence (empathy and flexibility) as a key factor in fair decision-making. The presence of women in leadership positions at DP2KB represents a successful model that breaks down cultural and structural barriers while strengthening the organization’s commitment to gender equality in public bureaucracy.